Amercan origins: tracing our Jewish roots - Sagan, Miriam, 1954- (Santa Fe, N.M. : J. Muir Publications ; New York : distributed to the book trade by W.W. Norton & Co., 1993)
Traces the history of Jews, especially those from Eastern Europe, in the United States, their experiences as immigrants, and their contributions to American culture.
Includes index.
Keywords: Jews -- United States -- History -- Juvenile literature; Jews, East European -- United States -- History -- Juvenile literature; Jews -- Europe, Eastern -- History -- Juvenile literature; Immigrants -- United States -- History -- Juvenile literature; Jews -- United States -- History; Jews, East European; United States -- Ethnic relations -- Juvenile literature; Europe, Eastern -- Ethnic relations -- Juvenile literature; United States -- Emigration and immigration